Low expression of HIF1AN accompanied by less immune infiltration is associated with poor prognosis in breast cancer - Tang, Shasha; Liu, Dongyang; Fang, Yuan; Yong, Liyun; Zhang, Yi; Guan, Mengying; Lin, Xiaoyan; Wang, Hui; Cai, Fengfeng (Frontiers in Oncology, 2023)
Hypoxia-inducible factor 1-alpha (HIF-1α) stability and transcriptional action are reduced by the hypoxia-inducible factor 1-alpha subunit suppressor (HIF1AN). Its inappropriate expression is associated with the development of cancer and immune control. It is yet unknown how HIF1AN, clinical outcomes, and immune involvement in breast cancer (BC) are related. Using the GEPIA, UALCAN, TIMER, Kaplan-Meier plotter, and TISIDB datasets, a thorough analysis of HIF1AN differential expression, medical prognosis, and the relationship between HIF1AN and tumor-infiltrating immune cells in BC was conducted. Quantitative real-time PCR (qRT−PCR) analysis of BC cells were used for external validation. The findings revealed that, as compared to standard specimens, BC cells had significantly lower levels of HIF1AN expression. Good overall survival (OS) for BC was associated with higher HIF1AN expression. Additionally, in BC, the expression of HIF1AN was closely associated with the chemokines and immune cell infiltration, including neutrophils, macrophages, T helper cells, B cells, Tregs, monocytes, dendritic cells, and NK cells. A high correlation between HIF1AN expression and several immunological indicators of T-cell exhaustion was particularly revealed by the bioinformatic study. HIF1AN is a predictive indicator for breast tumors, and it is useful for predicting survival rates.